2018
DOI: 10.3390/robotics7020023
|View full text |Cite
|
Sign up to set email alerts
|

Simple Reflex Controller for Decentralized Motor Coordination Based on Resonant Oscillation

Abstract: This article describes an extremely simple controller as a minimal example of decentralized motor coordination and gait generation. The control strategy is based on the stretch reflex in animals and requires no mutual communication or detailed body models. Despite such simplicity, each controller can sync itself and generate various resonant oscillation by only physical interaction through whole body dynamics. To evaluate this controller, we conduct some simulations with a linear spring-mass-damper system and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Because the oscillator adjusted its phase according to the reaction forces from the environment, a precise model and rigorous computation were not required. Motivated by this result, we previously proposed a simple controller [9] that autonomously synchronizes some entire mechanical systems to the natural vibration mode, which also only uses the surrounding force information. However, there is a limitation to implementing many decentralized controllers in general mechanical systems because each oscillator needs a sensor, a microprocessor, and some peripheral circuits.…”
Section: Introductionmentioning
confidence: 99%
“…Because the oscillator adjusted its phase according to the reaction forces from the environment, a precise model and rigorous computation were not required. Motivated by this result, we previously proposed a simple controller [9] that autonomously synchronizes some entire mechanical systems to the natural vibration mode, which also only uses the surrounding force information. However, there is a limitation to implementing many decentralized controllers in general mechanical systems because each oscillator needs a sensor, a microprocessor, and some peripheral circuits.…”
Section: Introductionmentioning
confidence: 99%
“…Open data platforms, for example, require a DSM that includes interactions across multiple build systems and loads, which must operate as a single, interconnected system for optimal performance. The MAS coordination system must be aware of all these systems and be able to exchange information between agents associated with the systems and devices [ 163 ].…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Multi-agent systems may enhance building control and management as building function and tenant usage change over time. In addition, the authors [ 163 ] demonstrated that intelligent MAS control could save 20% more energy than traditional thermal management.…”
Section: Application Of Agents In Sgsmentioning
confidence: 99%
See 1 more Smart Citation